Tracing The Footsteps Of Religious Extremism: Understanding Social Impact And Alternative Solutions - Fuwa, Muhamad Nur Faizi Putra; Dahrul Safitri; Dedi Ardiansyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2024)
Religious extremism has become one of the most serious challenges in contemporary society. When individuals or groups adopt radical and fanatical views of their religion, the consequences can have a negative impact on peace, tolerance, and social stability. In this article, the authors identify several factors that play a role in the rise of religious extremism. These factors include, but are not limited to, socio-economic inequality, lack of education, inter-religious tensions, political manipulation, and the influence of social media. Apart from that, this article also reviews how a wrong understanding of religion and narrow interpretation can lead to extremism. Understanding religion, accompanied by a dialogical approach regarding respect for differences in beliefs, will be emphasized as a way to overcome religious extremism. To find the root of the problem, further research is needed regarding the prevention efforts that have been carried out by the government, civil society, and religious organizations. The focus is on education, interfaith dialogue, and social development programs that seek to address the roots of problems and prevent radicalization. This article concludes by emphasizing the importance of collective awareness and global cooperation in confronting religious extremism. By addressing the root of the problem and trying to prevent the process of radicalization, society can achieve peace, harmony, and better interfaith understanding.